2022
DOI: 10.1002/cac2.12359
|View full text |Cite
|
Sign up to set email alerts
|

Non‐small cell lung cancer in China

Abstract: In China, lung cancer is a primary cancer type with high incidence and mortality. Risk factors for lung cancer include tobacco use, family history, radiation exposure, and the presence of chronic lung diseases. Most early‐stage non‐small cell lung cancer (NSCLC) patients miss the optimal timing for treatment due to the lack of clinical presentations. Population‐based nationwide screening programs are of significant help in increasing the early detection and survival rates of NSCLC in China. The understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
127
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(129 citation statements)
references
References 300 publications
1
127
0
1
Order By: Relevance
“…It is now confirmed that epidermal growth factor receptor (EGFR), coat protein complex I, and Ezrin/Radixin/Moesin proteins interact with TMEM16A to regulate the rapid proliferation and migration of cancer cells jointly . Studies show that TMEM16A regulates cancer cell growth through EGFR/SATA3, Ras–Raf–mitogen-activated protein kinase (MEK)–extracellular-signal-regulated kinase (ERK), and other signaling pathways. , In addition, TMEM16A also controls the growth of cancer cells by regulating cell osmotic pressure and membrane potential through transport of intracellular Cl ‑ . , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now confirmed that epidermal growth factor receptor (EGFR), coat protein complex I, and Ezrin/Radixin/Moesin proteins interact with TMEM16A to regulate the rapid proliferation and migration of cancer cells jointly . Studies show that TMEM16A regulates cancer cell growth through EGFR/SATA3, Ras–Raf–mitogen-activated protein kinase (MEK)–extracellular-signal-regulated kinase (ERK), and other signaling pathways. , In addition, TMEM16A also controls the growth of cancer cells by regulating cell osmotic pressure and membrane potential through transport of intracellular Cl ‑ . , …”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer has long been the leading cause of cancer morbidity and mortality . Although lung cancer causes more deaths than breast, prostate, and pancreatic cancers combined, the overall lung cancer mortality rate has declined over the past 20 years. , This mainly benefits from the early screening of lung cancer, thoracoscopy surgery, the decline in the number of smokers, and the improvement of molecularly targeted drugs and various adjuvant treatment options . Because of the increasing number of early-stage patients diagnosed by cancer screening, the cure rate of comprehensive treatment methods combining surgery, radiotherapy, chemotherapy, and various adjuvant treatments is increasing year by year …”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the common malignant tumor and displays the highest mortality rate ( Chen P. et al, 2022 ; Choi and Mazzone, 2022 ). Lung cancer had 1.8 million deaths (18% of the total cancer-related deaths) worldwide in 2020 ( Sung et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is a leading cause of cancer-related deaths worldwide (1). Non-small cell lung cancer (NSCLC) accounts for >75% of all cases of lung cancer and can be further classified into 3 subtypes; that is, adenocarcinoma (AC), squamous cell carcinoma (SCC), and large cell carcinoma (2)(3)(4)(5). A number of studies have successfully applied molecular-targeted therapeutic agents and d e m o n s t r a t e d t h e i r s u p e r i o r i t y t o c o n v e n t i o n a l chemotherapy in treating NSCLC (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%